2022
DOI: 10.1192/bjp.2022.7
|View full text |Cite
|
Sign up to set email alerts
|

Classification of suicidal thoughts and behaviour in children: results from penalised logistic regression analyses in the Adolescent Brain Cognitive Development study

Abstract: Background Despite efforts to predict suicide risk in children, the ability to reliably identify who will engage in suicide thoughts or behaviours has remained unsuccessful. Aims We apply a novel machine-learning approach and examine whether children with suicide thoughts or behaviours could be differentiated from children without suicide thoughts or behaviours based on a combination of traditional (sociodemographic, physical health, social–environmental, clinical psychiatric) risk facto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…However, the association between anxious depressive symptoms and suicidal thoughts became nonsignificant after adjusting for other symptoms and confounders. This result seems to be inconsistent with a previous cross-sectional study in which depression, among various risk factors including CBCL subscales, was found to predict suicidal thoughts and behaviors . The longitudinal nature of our study may partly explain this disparity, as we clustered anxious depressive symptoms into subgroups with different trajectories.…”
Section: Discussionmentioning
confidence: 70%
“…However, the association between anxious depressive symptoms and suicidal thoughts became nonsignificant after adjusting for other symptoms and confounders. This result seems to be inconsistent with a previous cross-sectional study in which depression, among various risk factors including CBCL subscales, was found to predict suicidal thoughts and behaviors . The longitudinal nature of our study may partly explain this disparity, as we clustered anxious depressive symptoms into subgroups with different trajectories.…”
Section: Discussionmentioning
confidence: 70%
“…Of the 20 selected studies, eight ( 51 58 ) investigated suicide-related outcomes in the general population [including two studies in youth ( 51 , 52 ) and two in elderly ( 57 , 58 )]. Six studies ( 59 64 ) focused on individuals with a diagnosis of major depressive disorder (MDD) or mood-related disorders [two recruited from psychiatric hospitals ( 61 , 63 ), one of antidepressant users recruited from either the Australian Genetics of Depression Study or through the nationwide Pharmaceutical Benefits Scheme database ( 62 )], two from the general population (i.e., UK Biobank participants that voluntarily enrolled in the study, and participants of the Brazilian Longitudinal Study of Adult Health, consisting of public institutions’ employees) that met criteria for common mental disorders ( 59 , 60 ), one from retrospective analysis of health record data ( 64 ), and one ( 65 ) focused on individuals diagnosed with multiple sclerosis.…”
Section: Resultsmentioning
confidence: 99%
“…Van Velzen et al ( 52 ) assessed n = 5,885 children also from the ABCD study ( 71 ). Binomial penalized logistic regressions were used to predict either parent- or child-reported suicidal thoughts and behaviors, recorded in the K-SADS.…”
Section: Resultsmentioning
confidence: 99%
“…This heterogeneity may explain why a singular brain-centric model of youth STBs has been elusive to date 7 . For example, when reduced thickness of left superior temporal sulcus was observed without considering subtypes in a prior ABCD-based analysis, the effect size was small 22 ; another machine learning study using the same ABCD data also reported low contribution of neuroimaging features to suicidal behavior prediction 23 , suggesting treating all suicidal children as one homogeneous group prevents identification of sensitive STBs biomarkers.…”
Section: Discussionmentioning
confidence: 99%